Effect of Molecular Order on the Performance of Naphthobisthiadiazole‐Based Polymer Solar Cells. Issue 6 (27th November 2013) - Sun, Yanming; Seifter, Jason; Wang, Ming; Perez, Louis A.; Luo, Chan; Bazan, Guillermo C.; Huang, Fei; Cao, Yong; Heeger, Alan J.
<x xml:space="preserve">Abstract</x> The influence of fullerene derivatives (PC60BM and PC70BM) and processing additives on the molecular order of a naphthobisthiadiazole‐based polymer (NT) in the blend films differ significantly. This is strongly associated with the bulk heterojunction (BHJ) solar cell performance and affects charge recombination rates and sweep‐out dynamics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>